KEBERADAAN AYAT MUHKAM DAN MUTASYABIH DALAM AL-QURAN - Syamsu Nahar (NIZHAMIYAH, 2016)
It has been understood that the Qur'an was revealed in Arabic. Therefore, to understand the laws in the texts of the Qur'an is necessary among other things in terms of language understanding in this matter is Arabic. The scholars who are experts in the field of usul fiqh, has conducted thorough research on the texts of the Qur'an, and the study was stated in the rules that hold true Muslims to understand the content of the Qur'an correctly. These rules help Muslims to understand the texts that appear vague (unclear), a global interpreting, takwil texts and other related legal decision from the texts of the Qur’an.Kata Kunci:  Muhkam, Mutasyabih, Al-Quran.